PENGARUH ATRIBUT PRODUK, HARGA DAN KETERLIBATAN KONSUMEN TERHADAP PERPINDAHAN MEREK BLACKBERRY KE SMARTPHONE SAMSUNG: Studi Kasus Konsumen Pada Kelurahan Rangkapan Jaya Baru Depok - Putri Nuraini, - (2019)
This study aims to analyze the brand switching of Blackberry smartphone brands to Samsung in Depok. The population of this study were residents of Rangkap Jaya Baru Depok Subdistrict and consumers of Samsung users with a sample size taken as many as 75 respondents with the criteria of someone who had transferred the BlackBerry smartphone brand to Samsung. The sampling technique uses a purposive sampling method. The analysis technique used is PLS (Partial Least Square) with SmartPLS 3.0 software. The results of this study show that (1) Product Attributes have a significant effect on the decision to move Samsung smartphone brands to iphone in Depok with a t test value of 3.365> 1.994 and a significant value of 0.001 <0.05, (2) Price has a significant effect on the smartphone brand transfer blackberry to samsung in Depok with a t-test value of 3.437> 1.994 and a significant value of 0.001 <0.05, (3) Consumer involvement has a significant effect on the transfer of blackberry smartphone brands to samsung in Depok with a t test value of 3.437> 1.994 and a significant value of 0.001 <0.05. The results of the determinant coefficient (R2) are 80.7% that the value of R-Square (R2)> 0.75 constructs product attributes, prices and consumer involvement.